Analisis Pengendalian Kualitas Produk Raja Kripik’s Di Kabupaten Sigi - Windi Mellyana; Sulaeman Miru; Suryadi Hadi (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This study aims to determine and analyze the quality control of banana chips in an effort to control the level of banana chip defects and whether the level of defects is within the control limits at Raja Kripik's IKM in Sigi Regency. Data collection methods using interviews, observation, and documentation. The data analysis technique uses the Statistical Quality Control (SQC) method using statistical tools in the form of check sheets and p-charts. The results of this study indicate that the product quality control carried out by Raja Kripik's is within the control limits because the value of the proportion of defects is smaller than the Upper Control Limit (UCL) value.